ADVANTAGES AND DISADVANTAGES OF NITRIC ACID PRODUCTION AT ATMOSPHERIC PRESSURE - D. J. Xujakulova; B. M. Aslonov; Sh.I.Istamov (Galaxy International Interdisciplinary Research Journal, 2024)
Nitric acid (HNO₃) production is widely used in industry and is primarily carried out through the Ostwald process. This process is of significant importance in the production of nitrogen-based fertilizers, explosives, and other chemical products.The Ostwald process is the main method for producing nitric acid and consists of the following stages: In the first stage, ammonia (NH₃) is catalytically oxidized with oxygen from the air. Catalysts such as platinum or ruthenium are used for this process. The reaction takes place at a temperature of 750-900°C and under high pressure (4-10 atm). As a result of the reaction, nitrogen oxide (NO) is formed.